The Phylogenetic Implications of the Mitochondrial Genomes of Macropsis notata and Oncopsis nigrofasciata - Wang, Jia-Jia; Wu, Yun-Fei; Yang, Mao-Fa; Dai, Ren-Huai (Frontiers in Genetics, 2020)
Macropsinae are forest pests that feed on woody plants. They can damage the growth of trees and crops, and some species can also spread plant pathogens. Due to their widespread effects, these leafhoppers are of great economic significance, which is why there is a need to study their genomes. To fill the gap in the mitochondrial genomic data of subfamily Macropsinae, we sequenced the complete mitochondrial genomes of Macropsis notata and Oncopsis nigrofasciata (which were 16,323 bp and 15,927 bp long, respectively). These two species are representative species of the leafhoppers group (Cicadellidae); the mitochondrial genomes of these species range from a length of 15,131 bp (Trocnadella arisana) to 16,811 bp (Parocerus laurifoliae). Both mitogenomes contained 37 typical insect mitochondrial genes and a control region; there were no long non-coding sequences. The genes within the mitogenome were very compact. The mitogenomes from both species contained two kinds of parallel repeat units in the control region. The whole mitogenomes of Macropsinae showed a heavy AT nucleotide bias (M. notata 76.8% and O. nigrofasciata 79.0%), and a positive AT Skew (0.15 and 0.12), and a negative GC Skew (-0.14 and -0.08). Upon comparative ML and BI analysis, some clade relationships were consistent among the six trees. Most subfamilies were reconstructed into monophyletic groups with strong support in all analyses, with the exception of Evacanthinae and Cicadellinae. Unlike the results of previous researches, although all Deltocephalinae species are grouped into one clade, they were not the sister group to all other leafhoppers. Further, Cicadellinae and Evacanthinae were occasionally reconstructed as a polyphyletic and a paraphyletic group, respectively, possibly due to the limited numbers of samples and sequences. This mitogenome information for M. notata and O. nigrofasciata could facilitate future studies on the mitogenomic diversity and evolution of the related Membracoidea, and eventually help to control their effects on plants for the betterment of the society at large.